Anaslisis Unsur Ekstrinsik Dalam Novel Elegi Tawa Niyusa Karya Lin Aiko - Debie Darbania; Alifiah Nurachmana; Partisia Cuesdeyeni; Linggua Sanjaya Usop; Nur Rahmawati; Repi Repi (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2023)
This research has specific objectives, namely (1) Describing religious values in the novel Elegi Tawa Niyusa by Lin Aiko. (2) Describe the social values in the novel Elegi Tawa Niyusa by Lin Aiko. (3) Describe the cultural values in the novel Elegi Tawa Niyusa by Lin Aiko. (4) Describe the moral values in the novel Elegi Tawa Niyusa by Lin Aiko. The basic theory in this research is structuralism theory. Structuralism theory is seen as a literary approach that emphasizes the study of the relationship between the building blocks concerned. This type of research is qualitative research, qualitative research is a research procedure that produces descriptive data in the form of written or spoken words from people and observed behavior. The research method used in this research is descriptive analysis. The descriptive analysis method is a method carried out by describing the facts which is then followed by analysis. Research methods such as reading techniques, recording things that are considered to contain religious values, social values, cultural values, moral values in the novel Elegi Tawa Niyusa by Lin Aiko, analyzing the extrinsic elements in the form of religious values, social values, cultural values, moral values, concluding the results study. The data source used is a literary work in the form of a novel entitled Elegi Tawa Niyusa by Lin Aiko. The result of this research is the discovery of extrinsic elements contained in the novel, namely the values contained in the novel, namely religious values in the form of keeping prayers, surrendering to God, perfecting worship, being filial to parents. Social values in the form of an attitude of respect or appreciation, an attitude of caring for each other, an attitude of caring for or protecting each other, and empathy for fellow creatures created by God. Cultural values that take the form of free association. Moral values that take the form of responsibility. The conclusion is surrender to God, mutual respect or respect, avoid promiscuity, always be responsible for the actions or decisions you have chosen.